The influence of the God locus of control and halal awareness on consumer trust in halal products - Fahira, Fairuz; Al'Fadli, Althaf; Putri, Desi Sabela (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This study examines the impact of God's Locus of Control (individual perception of God's control) and Halal Awareness (awareness of product halalness) on consumers' trust in halal products. In a society increasingly conscious of the importance of meeting religious requirements in consumption, psychological factors such as God's Locus of Control and awareness of the halalness of products become relevant for examination. The study employs a quantitative approach, gathering data through questionnaires from respondents with experience or knowledge about halal products. The collected data was analyzed using regression techniques to assess the influence of God's Locus of Control and Halal Awareness on consumer trust levels. The research aims to provide deeper insights into the psychological factors shaping consumer confidence in halal products, with potential practical implications for businesses and marketers in developing more effective communication and marketing strategies, particularly in the context of halal products. Theoretically, this study can contribute to the literature on consumer behavior and factors influencing purchasing decisions, especially in halal products.